1996
DOI: 10.1038/bjc.1996.37
|View full text |Cite
|
Sign up to set email alerts
|

A late phase II study of RP56976 (docetaxel) in patients with advanced or recurrent breast cancer

Abstract: A late phase II clinical trial of RP56976 (docetaxel), derived from Taxus baccata was performed to evaluate anti-tumour activity, time to progression and clinical toxicity in patients with advanced or recurrent breast cancer. The patients, between 15 and 80 years old with performance status (PS) of 0-2, received at least two cycles of docetaxel 60 mg m-2 intravenously at 3-4 week intervals. Of the 81 patients enrolled, the 72 eligible for the study were given a total of 327 cycles, with a median of four cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…The significantly lower dosage of the drug used here is the most likely explanation for this inconsistency. A higher dose may be clinically more effective, since the anti-tumour activity of docetaxel probably depends on the dose (Fumoleau et al, 1993;Adachi et al, 1996;Dieras et al, 1996). However, higher doses of docetaxel could not be used given the results of phase I trails in Japan (Taguchi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly lower dosage of the drug used here is the most likely explanation for this inconsistency. A higher dose may be clinically more effective, since the anti-tumour activity of docetaxel probably depends on the dose (Fumoleau et al, 1993;Adachi et al, 1996;Dieras et al, 1996). However, higher doses of docetaxel could not be used given the results of phase I trails in Japan (Taguchi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials to date have demonstrated that docetaxel has significant and consistent anti-tumour activities in a variety of solid tumours, including breast cancer, non-small-cell lung cancer and ovarian cancer (Cerny et al, 1994;Francis et al, 1994;Adachi et al, 1996;Dieras et al, 1996;Kunitoh et al, 1996). With regard to PC, preclinical studies have shown docetaxel to be active in PC models (Bissery et al, 1991), and two clinical trials of docetaxel at 100 mg m Ϫ2 have demonstrated a promising anti-tumour activity in PC (Rougie et al, 1994;Abbruzzese et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that d-allose treatment enhanced the anticancer effects of docetaxel and may reduce the side effects of the chemotherapeutic drug by reducing the total dose of docetaxel required. Major toxicities of docetaxel are neutropenia, mucositis, peripheral neuropathy and pulmonary disorders (37). Concurrent radiation therapy may increase docetaxel toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary objective was to determine the pharmacokinetic profile of docetaxel in the combination. The starting docetaxel dose of 60 mg m 72 was selected on the basis of its known antitumour activity and good safety profile when administered as a single agent (Adachi et al, 1996). The dose of cyclophosphamide was fixed at 600 mg m 72 since this is the effective dose considered active while producing little toxicity in current protocols.…”
Section: Docetaxelmentioning
confidence: 99%
“…The reduced incidence and severity of docetaxel-related fluid retention in this and other recent studies is probably due to the routine administration of a 3-day corticosteroid premedication regimen (Riva et al, 1997). Docetaxel 60 mg m 72 was chosen as the starting dose in this study on the basis of its antitumour activity and tolerability as a single agent (Adachi et al, 1996). It was therefore not surprising that antitumour activity was observed at each docetaxel and cyclophosphamide dose level, and at all disease sites.…”
mentioning
confidence: 99%